Pengaruh Kenikmatan Yang Dirasakan, Kegunaan Yang Dirasakan Dan Niat Merekomendasikan Terhadap Minat Beli Perempuan Millenial Pengguna Tik Tok Di Kota Bengkulu - Ilahi, Dio Rahmat; Octaviani, Vethy; Sari, Sapta (UNIVED PRESS, Universitas Dehasen Bengkulu, 2023)
Tiktok social media is not only a medium for entertainment, but is considered effective enough to be relied on in finding information regarding many things such as promotional searches, this is due to the increasing popularity among Millennial women today. The popularity of Tiktok social media makes people easily involved and inspired to use the TikTok application. This study aims to determine the effect of perceived enjoyment, perceived usefulness and intention to recommend on consumer purchase intention of millennial women in Bengkulu City. The results of this study found that perceived enjoyment has a positive effect on the buying interest of millennial women in Bengkulu City, meaning that using TikTok can provide enjoyment and pleasure to Millineal women so that they have the intention to make a purchase. Perceived usefulness has a positive effect on the buying interest of Bengkulu City Millennial women, meaning that TikTok is very useful for Millineal women, especially in making online purchase transactions, Millennial women really feel the usefulness of TikTok for shopping and choosing the products they want in the TikTok application so they don't have to leave the house to shop. Intention to recommend has a positive effect on Buying Interest of millennial women in Bengkulu City, meaning that if Millennial women feel the benefits of using TikTok they will recommend TikTok to others either directly inviting others to use TikTok or recommending through their social media accounts that they are very satisfied using the TikTok application.